On the wings of moths: José Oiticica Filho's science and photography - Valentin, Andreas (ARS, 2015)
From the second half of the 1940s and more so in the 1950s, Brazilian photography renewed itself, initially within the photoclub circuits, in particular the Foto Cine Clube Bandeirantes in São Paulo, and later in the context of Brazilian constructivist movements. In this scenario, stands out the work of entomologist and photographer José Oiticica Filho (1906-1964). Analyzed here is his photographic production, its close relationship to his scientific research and methods as well as his encounter with the Brazilian Concrete and Neoconcrete Movements. Addressed also is the proximity of his work to the post-second World War German photography, particularly the fotoform and subjektive fotografie groups.